Teacher and Student Talk in Classroom - Amaliah Ramdani; Andi Hidayatul Mi'raj Mursyid (Fakultas Tarbiyah IAIN Fattahul Muluk Papua, 2022)
This research's main objectives aimed at describing the types of an effective teacher and student talk based on Moskowitz’s FLINT analysis system; and the factors influencing its use in the teaching and learning process. The researcher applied a qualitative research design. This research participants were the teacher and students of the English Education Study Program at the State University of Makassar. One teacher and two classes were taken as the subject of this research. The data were obtained from classroom observation and interviews. In the interview, 12 students were chosen randomly. The data from observation and interviews were analyzed using an interactive model of data analysis procedure based on Miles & Huberman (2013). The findings showed that not all types of an effective teacher and student talk occurred in the observation. Some utterances cannot be classified into FLINT theory, and those utterances were then classified as a new type of teacher talk: